What's Happening in the Missing Middle? : Lessons from Financing SMEs - Alibhai, Salman; Bell, Simon; Conner, Gillette (World Bank, Washington, DC, 2017)
Small and medium enterprises (SMEs) are the economic backbone of virtually every economy in the world. SMEs represent more than 95 percent of registered firms worldwide, account for more than 50 percent of jobs, and contribute more than 35 percent of Gross Domestic Product (GDP) in many emerging markets. Yet despite their vital role in almost every economy in the world, these enterprises remain significantly underserved by financial institutions. In an effort to bridge this financing gap, the World Bank Group works across a number of its Global Practices – and in conjunction with the International Finance Corporation’s Financial Institutions Group (FIG) and Cross-Cutting Advisory Services – to provide support to SMEs Bringing together the diverse expertise and perspectives of staff working across the institution, this compendium of lessons illuminates the World Bank Group`s experience with SMEs, exploring its policies and frameworks to support SMEs, analyzing innovations in the SME finance realm, and describing some country specific examples. These lessons will provide SME practitioners with practical guidance for their work with the SME sector, and will also inform and educate policymakers about interventions and approaches that they can consider.